KUFAN HADITH TRANSMITTERS AND GEOPOLITICS IN EARLY PERIOD OF ISLAM - Novizal Wendry; Abdul Majid; Susilawati Susilawati (ULUL ALBAB Jurnal Studi Islam, 2020)
This article discusses the hadith transmitters involvement in Kufa politic dynamic in the early time of Islam Period, which was experiencing a long range of social turmoils. These turmoils occurred from 40 H/661 AD until the end of the Umayyad dynasty in 125 H/743 AD. This article adopts a historical approach to conceive of the dynamic of politics among the hadith transmitters. This research revealed that the hadith transmitters built the city of Kufa. The behavior related to discrimination toward the opponents and the disappointments on the Umayah Dynasty triggered many rebellions such as al-Ḥusayn ibn ‘Alî ibn Abî Ṭâlib, Ibn al-Zubayr, Mukhtâr al-Thaqafî, al-tawwâbûn, and Zayd ibn ‘Alî. These turmoils involved Sa‘d ibn Abî Waqqâṣ and al-Mughîrah ibn Shu‘bah. We argue that the hadith transmitter influenced the hadiths they narrated. Based on the investigation of the two hadith contents that they narrated indicated that they took the side of the Mu‘âwiyah Dynasty and ‘Alî’s followers as the opponents.